How do parents access, appraise, and apply health information on early childhood allergy prevention? A focus group and interview study - Lander, Jonas; Bitzer, Eva Maria; von Sommoggy, Julia; Pawellek, Maja; Altawil, Hala; John, Cosima; Apfelbacher, Christian; Dierks, Marie-Luise (Frontiers in Public Health, 2023)
Background: When parents want to make health-related decisions for their child, they need to be able to handle health information from a potentially endless range of sources. Early childhood allergy prevention (ECAP) is a good example: recommendations have shifted from allergen avoidance to early introduction of allergenic foods. We investigated how parents of children under three years old access, appraise and apply health information about ECAP, and their respective needs and preferences. Methods: We conducted 23 focus groups and 24 interviews with 114 parents of children with varied risk for allergies. The recruitment strategy and a topic guide were co-designed with the target group and professionals from public health, education, and medicine. Data were mostly collected via video calls, recorded and then transcribed verbatim. Content analysis according to Kuckartz was performed using MAXQDA and findings are presented as a descriptive overview. Results: Parents most frequently referred to family members, friends, and other parents as sources of ECAP information, as well as healthcare professionals (HCPs), particularly pediatricians. Parents said that they exchanged experiences and practices with their peers, while relying on HCPs for guidance on decision-making. When searching for information online, they infrequently recalled the sources used and were rarely aware of providers of “good” health information. While parents often reported trying to identify the authors of information to appraise its reliability, they said they did not undertake more comprehensive information quality checks. The choice and presentation of ECAP information was frequently criticized by all parent groups; in particular, parents of at-risk children or with a manifested allergy were often dissatisfied with HCP consultations, and hence did not straightforwardly apply advice. Though many trusted their HCPs, parents often reported taking preventive measures based on their own intuition. Conclusion: One suggestion to react upon the many criticisms expressed by parents regarding who and how provides ECAP information is to integrate central ECAP recommendations into regular child care counselling by HCPs – provided that feasible ways for doing so are identified. This would assist disease prevention, as parents without specific concerns are often unaware of the ECAP dimension of issues such as nutrition.